2019
DOI: 10.1039/c8nr09855g
|View full text |Cite
|
Sign up to set email alerts
|

The role of surface chemistry in serum protein corona-mediated cellular delivery and gene silencing with lipid nanoparticles

Abstract: The distinct protein corona fingerprint on lipid nanoparticles of different surface characteristics affected cellular transfection and gene silencing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
92
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(98 citation statements)
references
References 54 publications
6
92
0
Order By: Relevance
“…Of note, in such stem-cell derived hepatic cells addition of LNP-siRNA resulted in efficient TTR knockdown in the absence of serum proteins present in standard cell culture media suggesting that intrinsic APOE secretion by hepatic cells is sufficient for uptake of Patisiran. Our results are in line with the general view that a subset of ionisable LNP formulations, i.e., containing DLin-MC3-DMA, requires APOE for efficient hepatocyte delivery [10,18,20]. There are several lines of evidence suggesting that APOE is important for LNP-siRNAs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Of note, in such stem-cell derived hepatic cells addition of LNP-siRNA resulted in efficient TTR knockdown in the absence of serum proteins present in standard cell culture media suggesting that intrinsic APOE secretion by hepatic cells is sufficient for uptake of Patisiran. Our results are in line with the general view that a subset of ionisable LNP formulations, i.e., containing DLin-MC3-DMA, requires APOE for efficient hepatocyte delivery [10,18,20]. There are several lines of evidence suggesting that APOE is important for LNP-siRNAs.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we confirmed by in vitro experiments that expression of APOE is a major determinant of Patisiran-mediated knockdown. Human hepatoma cell line HepG2 was chosen which was previously used to evaluate other siRNAs and various LNP formulations [19,20]. Our data indicate that downregulation of APOE significantly deteriorates silencing of TTR.…”
Section: Discussionmentioning
confidence: 97%
“…The radiotherapy resistance of HCC is mainly due to the occurrence of epithelial-mesenchymal transition (EMT) and cross-activation of Ras/Raf and phosphatidylinositol 3kinase (PI3K)/Akt/mTOR pathways in HCC [27,28]; excessive activation of the pathway can enhance HCC cell survival and inhibit cell death. Inhibition of Ras/Raf and PI3K/Akt/mTOR pathways regulates cell cycle of HCC, inhibits cell proliferation, promotes apoptosis, and enhances radiosensitivity of HCC [28][29][30]. BEZ235 (PI3K/mTOR pathway inhibitor) causes significant cell death [29][30][31], but low concentrations of the drug in the target tissue results in poor therapeutic efficacy and need for more frequent dosing; on the other hand, high drug concentrations may cause toxicity, including stomatitis, hyperglycemia, non-infectious pneumonia, and immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of Ras/Raf and PI3K/Akt/mTOR pathways regulates cell cycle of HCC, inhibits cell proliferation, promotes apoptosis, and enhances radiosensitivity of HCC [28][29][30]. BEZ235 (PI3K/mTOR pathway inhibitor) causes significant cell death [29][30][31], but low concentrations of the drug in the target tissue results in poor therapeutic efficacy and need for more frequent dosing; on the other hand, high drug concentrations may cause toxicity, including stomatitis, hyperglycemia, non-infectious pneumonia, and immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…This concept of PEG capable of manipulating the PC emerges in another study by Chen et al (2019), in which the different composition and coating of siRNA-loaded solid lipid NPs (SLNs) could modulate the composition of PC, with either positive or negative repercussions on the cellular uptake rate and efficacy. In this study, particles were functionalized with different ratios of either C14-PEG or C18-PEG.…”
Section: Synthetic Approachesmentioning
confidence: 99%